PENGARUH FUNGI Aspergillus flavus, Aspergillus terreus, DAN Trichoderma harzianum TERHADAP PERTUMBUHAN BIBIT Avicennia officinalis - Indah K Sihombing; Yunasfi Yunasfi; Budi Utomo (Program studi Kehutanan USU, 2015)
Mangrove has the ability to absorb organic and inorganic from environment. Fungi in mangrovecan decompotition of litter and neutralize the accumulation of heavy metals. This research can provide information on the types of fungi are able to increase growth of seedlingA. officinalis. This research was conducted from October 2014 until January 2015 using a completely randomized design (CRD) with treatment application three types of fungi and five replications. There are three types of fungi namely appliedA. flavus, A.tereus and T. harzianum. Application ofT. Harzianumgave the best result on seedling growth parameter of A. Officinaliswith an average height 26.04 cm, application of A. Flavusgave the best diameter growth, the best leaf area and total dry weight of A. Officinaliswith an average diameter 0.62 cm, leaf area total 66238,6 cm2 and total dry weight 2.82 g, higher than the average of control.Keywords: Avicennia officinalis, fungi, mangrove, acumulation